Penyuluhan Tentang Pertolongan Pertama Pada Kecelakaan Anak - Purnawan, Iwan; Wirakhmi, Ikit Netra (Jurnal of Community Health Development, 2021)
The accident rate in elementary school-aged children is quite high. Efforts that can be made to overcome this are by providing health education in the form of counseling to parents about First Aid in Child Accidents. The purpose of this activity is to provide knowledge to participants so that they can perform first aid in child accidents. This program is implemented through health education with lectures and discussions. The participants were 10 committee members of Al Izzah Islamic Elementary School, Purwokerto. The value of knowledge is measured before and after education. The average value of the pre test is 64.00 while the average value of the post test is 86.00. The results of the paired t-test analysis showed that the value of p = 0.001 indicated that there was a significant relationship or difference between the knowledge scores of respondents and their understanding of first aid in child accidents before and after education.